1995
DOI: 10.1007/bf00196351
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HIV-1 expression by HIV-2

Abstract: HIV-1 and HIV-2 are co-endemic in certain geographic areas. HIV-2 is more weakly pathogenic than HIV-1, and progression to AIDS occurs less frequently and over a longer period of time. Recent epidemiologic studies suggest that individuals infected with HIV-2 have a lower risk of HIV-1 infection. Both immune mechanisms and various modes of viral interference have been proposed to account for these results. Our findings, described in this paper, suggest that HIV-2 inhibits HIV-1 replication. To study the molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 28 publications
(23 reference statements)
3
7
0
Order By: Relevance
“…Though the exact mechanism remains to be defined, the inhibition appeared to be mainly due to an intracellular molecular event because it could not be explained solely on the basis of cell surface receptor mediated interference. The results support the notion that the inhibition likely occurred at the level of viral RNA, possibly involving competition between viral RNAs for some transcriptional factor essential for virus replication [77,78].…”
Section: F2 In Vitro Correlates Of Hiv-2 Protectionsupporting
confidence: 84%
“…Though the exact mechanism remains to be defined, the inhibition appeared to be mainly due to an intracellular molecular event because it could not be explained solely on the basis of cell surface receptor mediated interference. The results support the notion that the inhibition likely occurred at the level of viral RNA, possibly involving competition between viral RNAs for some transcriptional factor essential for virus replication [77,78].…”
Section: F2 In Vitro Correlates Of Hiv-2 Protectionsupporting
confidence: 84%
“…In contrast, a meta-analysis showed that HIV-2-infected individuals are more likely to acquire HIV-1 infection than HIV-negative individuals [38]. Several laboratory studies suggested that in dually infected individuals, HIV-2 exerted a possible inhibitory effect on HIV-1 disease progression [20,[40][41][42][43], but other studies found no effect of HIV-2 on the viral load of HIV-1 [34,44]. In this meta-analysis, we did not find evidence for an inhibitory effect, as there was no significant difference between mortality rates for HIV-D and HIV-1.…”
Section: Discussionmentioning
confidence: 83%
“…Further characterization of this factor, which appears to be necessary for Tat-2, but not necessarily for Tat-1 to transactivate through TAR-2, should yield insight into the differences between the mechanisms of action of Tat-1 and Tat-2 and into how the crucial Tat transactivators function in general. In view of recent reports that HIV-2 inhibits HIV-1 expression (50a), an effect perhaps mediated by TAR (36), an understanding of TAR-2-mediated transactivation may suggest therapeutic modalities for HIV-1, as well as for HIV-2.…”
Section: Mutation Of the 3 Arm Of The Promoter-proximal Stem-loop Affmentioning
confidence: 99%